Analysis The Effect Of Credit Interest Rates, Gross Domestic Product, And Inflation On Domestic Investment In Indonesia In 2000 – 2021 - Karel Milliano Hendika; Eni Setyowati (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2022)
Indonesia as a developing country certainly depends on investment because it is the first step to do development. Investment in the form of investment is considered to solve several economic problems, such as economic crises, and other economic challenges. One of the investments in Indonesia is capital investment, which is the realization of domestic investment. There are several factors that affect domestic investment, such as credit interest rates, gross domestic product and inflation. This study aims to analyze these factors on domestic investment in Indonesia from 2000 to 2021. This study used regression analysis method Ordinary Least Square (OLS). The results showed that partially variable variable lending rates and gross domestic product have a negative influence on domestic investment, while the inflation variable has a positive influence.